Magnetic Behavior of Ni/NiO CoreâShell Nanoparticles under Electromagnetic Waves for OilâWater Interfacial Tension Reduction - Baig, M.K. (Springer New York LLC, 2019)
The increasing demand for oil and gas has led to a hope of developing more efficient recovery methods. It is well known that nanoparticles adsorbed at the oilâwater interface, but there is no consensus that has been reached on whether magnetic nanoparticles under electromagnetic waves affect the interfacial tension. In this paper, nickel/nickel oxide nanoparticles have been synthesized using solâgel auto combustion method. The product was characterized using x-ray diffraction, Raman spectroscopy, field emission scanning electron microscopy, Fourier transforms infrared spectroscopy and vibrating sample magnetometer. The results show the Ni/NiO phases and the ferromagnetic nature of the sample. The Ni/NiO nanofluids were prepared to investigate the effect on oilâwater interfacial tension in enhanced oil recovery under electromagnetic waves using an inverted pendant drop method. The results show a significant decrease in interfacial tension under electromagnetic waves of frequency 2.2Â kHz at low wt. of Ni/NiO and at room temperature. The decrease in the interfacial tension has been observed by increasing the temperature to 90Â Â°C using temperature controller. The decrease in the interfacial tension could be due to the interaction of oscillating B-field of waves and magnetic domains of adsorbing nanoparticles at the oilâwater interface which disturbed the oilâwater interface. Â© 2019, ASM International.